(3McGjI GdCbhGd GdYGUeI ef GdGYJRGd eeG EfJRY hLeY ef cJH GdEeGe YHO Gddg Hf MeRIs - (3fhQ GdOjf CHh YHO Gddg MejOGf Hf jMji Hf MejOGf GdbGSejs
(3ChdgG (B:s
(3CeG HYO aEfg deG XgQ cKjQ ef GdCbhGd GdJi EHJOYgG Cgd GdEYJRGd ai HYV ef jOYi Cfg ef TjYg GdEeGe GdefUhQ HGddg s
(3BNQgG (B:s
(3hMcGjJg Ydjg GdSdGe Yf GdEeGe CHj GdaJM Hf GdMSf GdOjdei Gfg bGd ai JaSjQ bhd Gddg JYGdi bGd GdEeGe Ydjg GdSdGe hgPG eYfi bhi YfOfG , hHg fbhd hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds